Challenges in Interpreting Leukocyte and Nucleated Red Blood Cell Counts in Neonatal Hemolytic Disease: A Case Report on Hematology Analyzer Performance: Leukocyte and Nucleated Red Blood Cell Counts in Neonatal Hemolytic Disease - Jakšić, Marina; Banjac , Lidija; Banjac , Boban (Journal of Medical Biochemistry, 2025)
Summary We present a case of hemolytic disease of the newborn (HDN) due to maternal alloimmunization with anti-E and anti-c antibodies, resulting in severe anemia, respiratory insufficiency, and hyperbilirubinemia in a term male neonate. Hematological evaluation using the automated analyzer Sysmex XN-3100 yielded an erroneously elevated white blood cell (WBC) count of 163 × 10⁹/L, later manually corrected to 28 × 10⁹/L due to extreme nucleated red blood cell (NRBC) interference (>2,000 NRBCs per 100 WBCs). This case illustrates the analytical limitations of modern hematology analyzers in neonates with pronounced erythroblastosis and emphasizes the essential role of manual peripheral blood smear review and interdisciplinary clinical-laboratory correlation in ensuring diagnostic accuracy.